The Pronunciation of the Hijaiyah Letters for Autistic Children at Extraordinary Islamic School Qothrunnada Yogyakarta - Nur Fauziah Alvin; Ferawati Ferawati (Al-Misbah (Jurnal Islamic Studies), 2020)
This research aims to describe the pronunciation of the hijaiyah letters for autistic children at Extraordinary Islamic School Qothrunnada, as well as explaining factors cause errors of pronunciation of the letters hijaiyah and changing meanings. Formal object in this research is the pronunciation of the hijaiyah letters. The object of the material in this study is an autistic children at Extraordinary Islamic School Qothrunnada. The methods used in the analysis of data is a method in accordance and its preliminary technique is the technique hear and technique chat. Through this study, the researchers found the hijiayah letters which undergoes changes, with the following details 1) change letter Ø« become Ø³, 2) change letter Ø° become ,Ø¯ 3) change letter Ø² become ,Ø¬ 4) change letter Ø´ become Ø³, 5) change letter Øµ become Ø³, 6) change letter Ø· become Øª, 7) change letter Ø¸ become Ø¶, 8) change letter Ø¹ becomeØ£ , 9) change letter Ù‚ become Ùƒ, 10) change letter ï»« become Ø, 11) change letter Ø¹ become nga. Factors cause changes in the sound is 1) Central System talk, 2) sound production system 3) the influence of first language, 4) articulation (makharijul huruf).